PERAN BUMDES DALAM MENJAGA KEBERLANJUTAN EKONOMI MASYARAKAT DESA PADA MASA PANDEMI - widiastuti, widiastuti; Arumdika, Yokhebed (Lembaga Penelitian dan Pengabdian Masyarakat, 2020)
BUM Desa, as the economic institution, could keep the continuity of rural society's economy on the pandemic situation. Still, the villagers did not respond yet that institutions and the other side, some BUMDesa did not succeed. The objection of the social service gives public and village officials information and added understanding about BUM Desa's role to keep the continuity of rural communities' economy. The method is carried out virtually. Base on the evaluation that counseling could add up understanding society's and village official about the role of human resources quality dan the trust for developed BUM Desa as a business entity for keeping the continuity economy of rural communities